2021
DOI: 10.1038/s41477-021-00856-7
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis bZIP19 and bZIP23 act as zinc sensors to control plant zinc status

Abstract: Zinc (Zn) is an essential micronutrient for plants and animals because of its structural and catalytic roles in many proteins. Zn deficiency affects ca. two billion people, mainly those living on plant-based diets that rely on crops from Zn deficient soils. Plants maintain adequate Zn levels through tightly regulated Zn homeostasis mechanisms, involving Zn uptake, distribution and storage, but it was not known how they sense Zn status. We use in vitro and in planta approaches to show that the Arabidopsis thali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 44 publications
3
98
1
Order By: Relevance
“…The AtbZIP19 and AtbZIP23 TFs from Arabidopsis are the best studied regulation system coordinating the zinc deficiency response in plants (Assunção et al, 2010; Lilay et al, 2021). Homologues with conserved functions were characterized in barley, wheat and rice (Castro et al, 2017; Evens et al, 2017; Lilay et al, 2020; Nazri et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AtbZIP19 and AtbZIP23 TFs from Arabidopsis are the best studied regulation system coordinating the zinc deficiency response in plants (Assunção et al, 2010; Lilay et al, 2021). Homologues with conserved functions were characterized in barley, wheat and rice (Castro et al, 2017; Evens et al, 2017; Lilay et al, 2020; Nazri et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Close homologs from Barley (HvbZIP56 and HvbZIP62, Nazri, Griffin, Peaston, Alexander‐Webber, & Williams, 2017), wheat (TabZIPF1 and TabZIPF4 , Evens, Buchner, Williams, & Hawkesford, 2017) and rice (OsbZIP48 and OsbZIP50, Lilay et al, 2020) could rescue an Arabidopsis bzip19bzip23 double mutant under zinc deficiency, suggesting a shared function in zinc homeostasis. The Cys‐/His‐rich motif of the AtbZIP19 and AtbZIP23 proteins is involved in zinc sensing via direct zinc binding, which inactivates these TFs under cellular zinc sufficiency (Assunção et al, 2013; Lilay et al, 2021; Lilay, Castro, Campilho, & Assunção, 2019). In order to discover proteins involved in zinc sensing and signalling in plants, the proteome dynamics upon zinc resupply in zinc‐deficient Arabidopsis plants was recently investigated (Arsova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although Lilay et al (2020) reported that OsbZIP48 , OsbZIP49 and OsbZIP50 were not differentially expressed after 21 days of Zn deficiency, our results showed differential expression of OsbZIP genes in response to both Zn treatments, indicating possible regulation of OsbZIPs by Zn at transcriptional level (Figure 3d). Recently, AtbZIP19 and AtbZIP23 have been reported to act as Zn sensors because they contain a Cys/His‐rich motif that can bind to Zn 2+ ions directly, and mutation of this motif perturbs Zn binding that in turn causes a constitutive transcriptional Zn deficiency response (Lilay et al, 2021). It can be implied that the activity of OsbZIP48, which shares the characteristic Cys/His‐rich motif with Arabidopsis AtbZIP19, may be regulated by Zn at protein level as well (Castro et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Under Zn starvation conditions, AtbZIP19 and AtbZIP23 promote Zn uptake by binding to the zinc deficiency response element (ZDRE) located in the promoter region of genes encoding Zn transporters such as the zinc‐regulated transporter/iron‐regulated transporter‐like protein family (ZIP transporters) and Zn chelators such as nicotianamine synthases (Assunção et al, 2010, 2013; Lilay, Castro, Campilho, & Assunção, 2019). Recently, AtbZIP19 and AtbZIP23 have been shown to act as Zn sensors because they contain a Zn sensor motif that can bind to Zn 2+ ions, and mutation of this motif affects Zn binding and eventually leads to a constitutive transcriptional Zn deficiency response (Lilay et al, 2021). The rice ( Oryza sativa ) F‐bZIP homologs OsbZIP48 and OsbZIP50 complemented the hypersensitivity of Arabidopsis bzip19bzip23 double mutants exposed to Zn deficiency, suggesting that F‐bZIP‐mediated Zn deficiency responses are conserved in Arabidopsis and rice (Lilay et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several transcription factors involved in Zn homeostasis belong to the F group of the basic-region leucine zipper (bZIP) factors and have histidine-rich motifs at their N-terminal region capable of Zn binding. Thus, bZIPs act as Zn sensors that are crucial in maintaining adequate Zn acquisition (Krishna et al, 2020, Lilay et al, 2021.…”
Section: Zincmentioning
confidence: 99%